Alterations in DNA methylation profiles in cancellous bone of postmenopausal women with osteoporosis. Issue 8 (26th June 2020) - Zhou, Yu; Yang, Ling; Wang, Hong; Chen, Xi; Jiang, Wei; Wang, Zhicong; Liu, Shuping; Liu, Yuehong
Abstract : Osteoporosis is characterized by systemic microarchitecture impairment and bone loss, which ultimately lead to fragility fractures. This disease is most common in older people, especially in postmenopausal women. Cancellous bone is affected by osteoporosis earlier than cortical bone, and DNA methylation microarray analysis of the hip cancellous bone of patients with osteoarthritis revealed differential methylation. In view of the important role of cancellous bone in bone development, we examined genome‐wide DNA methylation profiles in the cancellous bone from patients with postmenopausal osteoporosis versus healthy postmenopausal women using Illumina 850K methylation microarray analysis. Under a threshold of P  < 0.05, we obtained a total of 8973 differentially methylated genes, such as SOX6, ACE, SYK and TGFB3 . Under a threshold of P  < 0.05 and |△β| > 0.2, a total of 17 and 34 key differentially methylated genes were further identified at the promoter region and cytosine‐ phosphate‐ guanine (CpG) islands (such as PRKCZ, GNA11 and COL4A1 ), respectively. PLEKHA2, PLEKHB1, PNPLA7, SCD, MGST3 and TSNAX were the most common differentially methylated genes at both the promoter region and CpG islands. Five important signaling pathways, including the calcium signaling pathway, the cyclic guanosine phospho‐protein kinase G (cGMP‐PKG) signaling pathway, endocytosis, the Rap1 signaling pathway and the AMPK signaling pathway were identified. Our study may be suitable as a basis for exploring the mechanisms underlying osteoporosis in postmenopausal women. Abstract : We studied DNA methylation profiles of cancellous bone in postmenopausal women with osteoporosis. Thirteen differentially methylated genes, including PLEKHA2, PLEKHB1, PNPLA7, SCD, MGST3, TSNAX, PRKCZ, GNA11, COL4A1, SOX6, ACE, SYK and TGFB3, and five related signaling pathways (calcium, cGMP‐PKG, endocytosis, Rap1 and AMPK) were identified. Our study may facilitate the identification of a novel DNA methylation molecular mechanism underlying postmenopausal osteoporosis.